2015
DOI: 10.1103/physrevb.92.155113
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-silicene bilayer: A nanocapacitor with permanent dipole and piezoelectricity effect

Abstract: Using density functional theory, we study the electronic properties of a graphene-silicene bilayer (GSB). A single layer of silicene binds to the graphene layer with adhesion energy of about 25 meV/atom. This adhesion energy between the two layers follows accurately the well-known −1/z 2 dispersion energy as found between two infinite parallel plates. In small flakes of GSB with hydrogenated edges, negative charge is transferred from the graphene layer to the silicene layer, producing a permanent and a switcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…One of the key issues are to development of an appropriate material for nanocapacitors electrode, which should have large specific capacitance are poorly abundant. Given a great interest in nanocapacitors, we are going to employ studied systems as nanocapacitors. For this, we have calculated dipole moment P (D), stored charge Q s (|e|), stored energy E s (eV), and capacitance C (F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key issues are to development of an appropriate material for nanocapacitors electrode, which should have large specific capacitance are poorly abundant. Given a great interest in nanocapacitors, we are going to employ studied systems as nanocapacitors. For this, we have calculated dipole moment P (D), stored charge Q s (|e|), stored energy E s (eV), and capacitance C (F).…”
Section: Resultsmentioning
confidence: 99%
“…Supercapacitors and nanocapacitors are standouts among the most interesting electrical energy storage devices because of their high power density, operation in an extensive variety of temperatures, no memory impact, long life cycle, and great stability. The electronic double-layer capacitor (EDLC) known as supercapacitors, which can store energy in the form of electricity by the electrode–electrolyte interface under a bias voltage. It is conceivable to consider higher estimation of the capacitance of EDLC than a conventional dielectric capacitor, while in case of metal electrode, EDLC is extremely high because of the large electronic density of states at the Fermi level. Two-dimensional (2D) materials, such as graphene, in which quantum capacitance and EDLC have the same sequence of magnitude, thereby greatly influence the total capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, silicene‐based van der Waals heterostructures are predicted to have fascinating physical properties. The graphene‐silicene vertical heterostructure is predicted to be a promising candidate as anode material and nanocapacitor, and the silicene–arsenene vertical heterostructure is predicted to be useful in nanoelectronic and optoelectronic devices …”
mentioning
confidence: 99%
“…Moreover, silicene‐based van der Waals heterostructures, which have been studied theoretically, have not been experimentally demonstrated yet. Kiraly et al deposited carbon and silicon on Ag(111) surface and found both lateral and vertical graphene‐silicon heterostructures, but the Si atoms are sp 3 ‐bonded as in bulk crystalline Si, not silicene.…”
mentioning
confidence: 99%
“…The electric field and hence induced electrostatic charging are electronically the most interesting excitation, which can exfoliate single layers from multilayers, 40,41 control the adatom adsorption and desorption, 42,43 store energy [44][45][46] and tune the electronic structure [47][48][49] in 2D materials. Charging can be achieved by external electric field or by optical excitation, whereby valence electrons occupy conduction states by creating e-h pairs maintaining the charge neutrality.…”
Section: Temperature Strain and Charge Induced Phase Changesmentioning
confidence: 99%